2018
DOI: 10.1111/bcp.13492
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac output changes after osmotic therapy in neurosurgical and neurocritical care patients: a systematic review of the clinical literature

Abstract: AIMOsmotherapy constitutes a first-line intervention for intracranial hypertension management. However, hyperosmolar solutes exert various systematic effects, among which their impact on systemic haemodynamics is poorly clarified. This review aims to appraise the clinical evidence of the effect of mannitol and hypertonic saline (HTS) on cardiac performance in neurosurgical and neurocritical care patients. METHODA database search was conducted to identify randomized clinical trials and observational studies rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 41 publications
4
12
1
Order By: Relevance
“…In follow up of vital data we found there was no statistically significant difference in BP, HR and temperature. This result agree with systematic review and meta-analysis done Tsaousi et al (10) to show cardiac output changes after osmotic therapy in neurosurgical and neurocritical care patients, and concluded that mannitol induced a consistent MAP deterioration, which became apparent immediately after the end of the infusion and lasted up to 45 min, and reported this effect was not of statistical importance and also in HR.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In follow up of vital data we found there was no statistically significant difference in BP, HR and temperature. This result agree with systematic review and meta-analysis done Tsaousi et al (10) to show cardiac output changes after osmotic therapy in neurosurgical and neurocritical care patients, and concluded that mannitol induced a consistent MAP deterioration, which became apparent immediately after the end of the infusion and lasted up to 45 min, and reported this effect was not of statistical importance and also in HR.…”
Section: Discussionsupporting
confidence: 91%
“…): ROC curve of Right ONSD before and after mannitol therapy as a predictor of brain edema (2): ROC curve of left ONSD before and after mannitol therapy as a predictor of brain edema Table(10): ROC curve of left ONSD before and after mannitol therapy as a predictor of brain edema…”
mentioning
confidence: 99%
“…Hyperosmolar therapy constitutes the mainstay of medical interventions to control increased intracranial pressure (ICP), irrespective of etiology 1–3. Currently, mannitol and hypertonic saline (HTS) are the hyperosmolar solutions most extensively used in neurosurgical and neurocritical care practice to attenuate the intensity and duration of intracranial hypertension and thus improve cerebral perfusion and oxygen delivery 4,5. In addition, during craniotomy, reduction of brain water content facilitates brain relaxation before dural opening, improves brain elastance, optimizes surgical exposure, and attenuates brain retractor pressure 3,6,7…”
mentioning
confidence: 99%
“…[1][2][3] Currently, mannitol and hypertonic saline (HTS) are the hyperosmolar solutions most extensively used in neurosurgical and neurocritical care practice to attenuate the intensity and duration of intracranial hypertension and thus improve cerebral perfusion and oxygen delivery. 4,5 In addition, during craniotomy, reduction of brain water content facilitates brain relaxation before dural opening, improves brain elastance, optimizes surgical exposure, and attenuates brain retractor pressure. 3,6,7 HTS and mannitol share some common brain bulkreducing and ICP-lowering properties, among which the generation of osmotic fluid shifts, enhancement of cardiac output, improvement of capillary blood laminar flow, and dehydration of endothelial cells hold key roles.…”
mentioning
confidence: 99%
See 1 more Smart Citation